SOCIAL QUESTIONS OF CASTE AND GENDER IN THE CONTEXT OF LITERATURE - Mishra, Om (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In Indian society, caste has been given importance as a component of social structure. Classification of sub-castes under caste is also acceptable here. People living in Indian cities, towns and rural areas are seen following the system based here. Under the caste system, all the functions and rights of a person are determined by caste. Caste researchers have studied all aspects of caste structure, function, historical aspects etc. Dr. Srinivas (1955) believes that "In today's Indian society, castes are not the real unit but castes. Varna and caste are related to each other in the real social situation. Varna is related to social status. Everyone believes that Varna is related to the status of Brahmins and untouchables. All the castes between Brahmins and untouchables claim their social status from the viewpoint of Varna.1 Dr. G.S. Ghurye (1950) has mentioned 6 characteristics of caste system- 1. Segmental division of society, 2. Caste stratification, 3. Restrictions on food and social intercourse, 4. Socio-religious qualifications and privileges of different castes, 5. Absence of restricted choice of professions, 6. Restrictions related to marriage.2